PENGARUH INFLUENCER KULINER TIKTOK DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA UMKM KULINER DI MANOKWARI - Marchella C. T. Makabori Ang; Roberth Kurniawan Ruslak Hammar; Febianus Heatubun (JURNAL LENTERA BISNIS, 2026)
The rise of food influencers on TikTok has fundamentally altered how consumers discover and select food products, including within Manokwari's increasingly dynamic culinary MSME ecosystem. This study examines the partial and simultaneous effects of TikTok food influencer and brand awareness on consumer purchase decisions at culinary MSMEs in Manokwari. Employing a quantitative descriptive-associative approach with multiple linear regression, data were gathered from 100 respondents selected through purposive sampling using Likert-scale questionnaires. Respondents were consumers who had purchased culinary MSME products in Manokwari following exposure to TikTok food influencer content. Results show that: (1) TikTok food influencer positively and significantly affects purchase decisions (β=0.453; t=5.217; sig=0.000); (2) brand awareness positively and significantly affects purchase decisions (β=0.327; t=4.186; sig=0.000); (3) both variables jointly exert a significant effect (F=94.137; sig=0.000) with R²=0.659. TikTok food influencer proves to be the more dominant variable. These findings highlight the importance of collaboration between culinary MSMEs and local TikTok influencers as an effective digital marketing strategy, alongside the need to strengthen brand awareness through consistent brand identity and active digital platform presence.